DEVELOPMENT AND TRANSFORMATION OF RAVINE SISTEMS ON THE RIGHT BANK OF DNIPRO RIVER IN KYIV - ANATSKYI, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article examines the issues of impact that the city has on natural physical and geological phenomena; in particular, the author focuses his attention on erosive and gravitational processes occurring on the right bank of Dnipro River in Kyiv. Geological and geomorphological conditions of the area where Kyiv is located are favorable for such processes as river erosion, formation of ravines, planar erosion, landslides, etc. Special emphasis is made on human activity as the main factor which affects the area of human habitation.